Vulvovaginitis and inflammatory dermatoses - Camino, Gustavo (2015)
The high incidence of vulvovaginitis associated to contact dermatitis and chronic simple lichen motivated us to review these topics in this article. Guidelines for diagnosis and therapy are proposed for vulvovaginitits associated to dermatosis. Within the scope of differential diagnosis two less frequent diseases are mentioned - lichen escleroatrophicus and lichen planus-, emphasizing the planus-, emphasizing the devastating consequences that can arise by not doing an early diagnosis and therapy.